1999
DOI: 10.1021/jp991040w
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Photooxidation of CH3CN on TiO2

Abstract: The adsorption and photooxidation of CH3CN chemisorbed on TiO2 has been investigated using infrared spectroscopy. It was found that CH3CN forms an ice layer on TiO2 at 126K and above 126K CH3CN diffusion into TiO2 occurs. At 200K, the adsorption of CH3CN on both isolated Ti−OH groups and on the Ti4+ Lewis acid site was observed. Under UV irradiation (350 ± 50 nm; hυ = 3.10−4.13 eV), CH3CN was oxidized in the presence of O2 to form H2O, CO2, surface CO3 2- and an intermediate partially oxidized isocyanate speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
83
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 60 publications
11
83
1
Order By: Relevance
“…The CN -moiety renders it a particularly interesting molecule to examine, as it is representative of a number of toxic materials which are candidates for TiO 2 -based oxidation processes. However, to date, only a limited number of studies have appeared on the catalytic degradation of acetonitrile over TiO 2 either under dark conditions [6,7] or under UV irradiation [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CN -moiety renders it a particularly interesting molecule to examine, as it is representative of a number of toxic materials which are candidates for TiO 2 -based oxidation processes. However, to date, only a limited number of studies have appeared on the catalytic degradation of acetonitrile over TiO 2 either under dark conditions [6,7] or under UV irradiation [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The observation of the cyanogen moiety was considered as proof for the existence of the CN • radical, the latter being formed via a C-C bond breaking process. However, an IR study by Zhuang et al [11] later found that CH 3 CN was photooxidised over TiO 2 in the presence of oxygen to form H 2 O, CO 2 and surface CO 3 2-with an absorbed NCO intermediate. Additional information on the surface adsorption processes and surface products formed during photooxidation was also provided in a comprehensive study by Chuang et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated [11] that CH 3 CN adsorbed on Pt/SiO 2 could be -at least partly -hydrogenated. The formation of gaseous products and surface species in the UV irradiation of CH 3 CN adsorbed on TiO 2 has been studied in the presence [12] and in the absence [13] of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that CH 3 CN adsorbed on Pt/SiO 2 could be -at least partly -hydrogenated [14]. The UV irradiation of CH 3 CN adsorbed on TiO 2 in the presence of oxygen [15] led to the formation of H 2 O, CO 2 , surface CO 3 2-and surface isocyanate (NCO). The formation of surface CH 3 CONH 2 , η 2 (N,O)-CH 3 CONH, CH 3 COO (a) , HCOO (a) , NCO (a) and CN-containing species was observed, when the UV irradiation of CH 3 CN adsorbed on TiO 2 was performed in the absence of oxygen [16].…”
Section: Introductionmentioning
confidence: 99%